Indian summers. [videorecording (DVD)] The complete second season - Lloyd-Hughes, Henry, 1985-; West, Jemima, 1987-; Walters, Julie, 1950- (PBS Distribution, 2016)
It is 1935. Three years have passed, and as the seasons turn, so too do the machinations of a rising revolution. As a new summer falls upon the foothills of India's Little England, Simla, political tensions reach fever point. With help from the scheming Cynthia, Ralph faces the most pivotal year of his career. Alice's husband has followed her to India, and Aafrin's ascending career may be in jeopardy.